English pronunciation activity through PRONOUNCE / Siti Akmar Abu Samah and Umminajah Salleh - Abu Samah, Siti Akmar; Salleh, Umminajah (Universiti Teknologi MARA, Kedah, 2014)
The purpose of this study is to provide some creative strategies in acquiring correct English language pronunciation. Firstly, this paper shares an understanding on crucial articulation of the English phoneme /r/ by second language learners (SLL) among undergraduates, as part of its exploration on the pronunciation of the English words. The focus is also on the SLL’s realization of the phoneme – which they perceive to be correct – in initial, medial and final position. The qualitative approach is applied in the investigation, which looks into ways through which students acquire, among others include such variants of the /r/ phoneme in the course of their studies at the university. Data are collected by means of semi-structured questions distributed to forty first-year students pursuing undergraduate studies in a Malaysian university. The survey is conducted and responses analysed, using qualitative content analysis to identify major themes. The research finds that listening to dialogues in movies or listening to their favourite singers speaking, besides surfing websites, have an influence on the students’ pronunciation. Better understanding of such influences would provide language teaching practitioners some guidance to facilitate learning outcomes more effectively. This study serves to further explore the assumption that SLL learning interference has been evolving, which includes the influence of technology in the students’ daily process of learning. The study shows the importance of understanding such influences as a means to improve teaching and learning outcomes, in particular the strategy that is undertaken to improve pronunciation.